Influence of cereal legume rotation on soil chemical properties, crop yield and Striga control - Tarfa, B.; Kureh, I.; Kamara, A.; Maigida, D. (2006)
Integrated soil management with grain legumes was studied at two villages (Ugwan Shamaki) and Tashan Kaya) in Kaduna State, northern Guinea Savanna zone of Nigeria (190 day growing season). Impacts of one year rotation of Soybean and Cowpea on soil chemical properties were compared with sole maize and maize-cowpea mixture. All plots were Striga infested. Organic carbon decreased by 4 and 2% in maize after maize (SM) plots in Ugwan Shamaki and Tashan Kaya respectively. Sole soybean, SC and MC mixture increased organic carbon by 10, 2 and 23% in Ugwan Shamaki and 6, 4 and 16% in Tashan Kaya respectively. pH values were lowered in the order SM> MC>SS and SC. Exchangeable Ca, Mg and K remained unchanged or slightly increased. There was positive and significant association between pH and Striga parameters, while exchangeable bases had negative association with Striga parameters. Exchangeable K have positive and significant correlation with number of cobs at harvest (R = 0.68*), total cob weight (R = 0.61*) and maize grain yield (R = 0.64**) at Ugwan Shamaki. Maize yield increase from maize after Soybean were 150 and 301 kg over previous maize at Ugwan Shamaki and Tashan Kaya, respectively. Corresponding increases in Cowpea maize rotated plot in the two locations were 243 and 234 kg, respectively.